Efektifitas Penggunaan Multimedia Menggunakan Visual Basic For Application (VBA) Dalam Pembelajaran Matematika Ekonomi Pada Mahasiswa Program Studi Pendidikan Matematika FKIP UNISMA - Hasana, Siti Nurul; Alifiani, Alifiani (JU-ke: Jurnal Ketahanan Pangan, 2018)
The purposes of this study are to create a learning multimedia with Microsoft Power Point-based using Visual Basic for Application (VBA) as well as to describe the effectiveness of its application in learning Mathematics of Economy both quantitatively and qualitatively. Mathematics of Economy is a subject studied by 4th semester students of Mathematics Education study program in Teacher Training and Education Faculty of University of Islam Malang. The effectiveness is assessed from two factors, they are studentâs learning outcome and studentâs learning motivation. This study gives an alternative in learning Mathematics of Economy which is more attractive and more interactive. By using this multimedia in the class, the learning materials will be easier to be understood so that the studentâs learning outcome and learning motivation can be improved. The result of the quantitative analysis shows that the students in the class where the learning multimedia with Microsoft Power Point-based using VBA is applied have better learning outcomes than students with conventional learning method in the class. While the results of observation and interview as the way to do the qualitative analysis shows that learning motivation is improved in the class where the learning multimedia with Microsoft Power Point-based using VBA is applied.